Community-Based Da'wah after Hajj: Social Roles of Pilgrims in a Multicultural Society - Hamid, Noor (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study investigates the post-Hajj da'wah initiatives of the Indonesian Hajj Brotherhood Association (IPHI), with a focus on its role in fostering social cohesion and community empowerment among Hajj alumni in a pluralistic society. While existing research on Hajj pilgrimage has primarily centered on ritual dimensions or state regulation, little attention has been given to the post-pilgrimage civic and da'wah activities facilitated by community-based organizations such as IPHI. Addressing this gap, the study explores how IPHI Kapanewon Tempel functions as a local model of religious engagement and social mobilization after Hajj. Employing a qualitative case study approach, this research highlights the selection of IPHI Tempel due to its active engagement in grassroots da'wah and intergroup dialogue. The findings reveal that IPHI not only reinforces Islamic values among returning pilgrims but also contributes to broader social harmony through inclusive educational and social programs. This study offers a novel perspective by framing post-Hajj religious activism as a form of localized civic da'wah, thus expanding the discourse on pilgrimage beyond its ritual boundaries. The research contributes to understanding how religious organizations transform spiritual experiences into sustained community action in multicultural contexts.